Antiepileptic Potential of Justicia insularis Leaf Extract in Swiss Mice - Elkanah, Nancy; Nnumolu, Michael Chuks; Okokon, Jude Effiom; Ise, Uduak Peter (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Epilepsy is a prevalent neurological condition characterized by repetitive seizures, necessitating the exploration of efficacious treatments. Justicia insularis, a plant with a historical use in treating convulsions and epilepsy, has garnered attention as a potential antiepileptic agent. This study aimed to investigate the antiepileptic properties of Justicia insularis leaf extract, focusing on generated seizure models in mice. The analysis of variance (ANOVA), specifically one-way ANOVA, was utilized to assess the statistical significance of the data. Seizure models were employed to evaluate the antiepileptic effects of Justicia insularis leaf extract. The p-values obtained from the one-way ANOVA were significant, with values of ap<0.005, bp<0.01, and cp<0.001. These results suggest the statistical significance of the observed effects in the seizure models. This study provides valuable insights into the therapeutic potential of Justicia insularis leaf extract as a treatment for epilepsy. The significant findings underscore the importance of further research into the use of natural medicines for managing epilepsy, potentially offering new avenues for treatment.